Growth Differentiation Factor-15 as a Candidate Biomarker in Gynecologic Malignancies: A Meta-analysis. (26th November 2022) - Roy, Dipayan; Modi, Anupama; Purohit, Purvi; Khokhar, Manoj; Goyal, Manu; Sharma, Shailja; Setia, Puneet; Facciorusso, Antonio; Sharma, Praveen
Abstract: Growth differentiation factor-15 (GDF-15), though emerged as a novel marker in gynecological cancers, is yet to be recognized in clinical diagnostics. Eligible studies were sorted from multiple online databases, namely PubMed, Cochrane, ClinicalTrials.gov, Google Scholar, Web of Science, Embase, Scopus, LILACS, and Opengrey. From six studies, histopathologically diagnosed cases without prior treatment, and with diagnostic accuracy data for GDF-15 in gynecological cancers, were included. Our meta-analysis shows that GDF-15 has pooled diagnostic odds ratio of 12.74 at 80.5% sensitivity and 74.1% specificity, and an area under the curve of 0.84. Hence, GDF-15 is a potential marker to differentiate gynecological malignancy from non-malignant tumors.